Effect of Motivational Interviewing Counseling Model On Toothbrushing Practice Among Adolescents - Ulliana -; Masrifan Djamil; Bedjo Santoso; Ari Suwondo Suwondo; Sulur Joyo Sukendro (Journal of Applied Health Management and Technology, 2022)
Adolescence is characterized by a period of significant dental caries activity. research has proven that the level of caries in adolescence tends to have a high prevalence. One of the factors causing caries is the lack of awareness of adolescents in maintaining oral and dental hygiene, to increase awareness of adolescents can be done by promoting dental health through dental health education. Conventional dental health education that has been applied only focuses on increasing patient awareness of the severity of a disease problem through providing information/advice. The selection of the right approach in the process of delivering dental health education materials to adolescents is the intervention of the motivational interviewing counselling model.This study aims to determine the effectiveness of the motivational interviewing (MI) counselling model to improve teeth brushing practice in adolescents. Research methods research and development (RD) there are five stages of research, namely: information collection, model design, expert validation, and a trial model sample of 80 teenage students. Sampling using a purposive sampling technique. Data were tested using intraclass correlation coefficient, paired sample test and independent sample test. The results showed that the motivational interviewing counselling model intervention had the potential to improve teeth brushing skills in adolescents (p=0.001) and reduce plaque index scores (p=0.001). The conclusion shows that the MI counselling model is effective as a method of health education.